Virtual Public Space as a Medium for Conveying Aspirations and Criticism by the People of Surakarta City (Qualitative Study on Twitter Account @gibran_tweet) - Arlisa Ratnastuti; Mahendra Wijaya; Prahastiwi Utari (Formosa Journal of Social Sciences (FJSS), 2023)
This research will look at how people utilize social media as a virtual public space in communicating with the Government, including in terms of conveying aspirations and criticisms.  This phenomenon is also seen from the utilization of social media by the people of Surakarta City to convey aspirations and criticisms related to Surakarta City to the Mayor of Surakarta, Gibran Rakabuming Raka through the Twitter social media platform @gibran_tweet.   This research uses descriptive qualitative research methods to examine the problem under study. The data used is contextual data seen through the Twitter account @gibran_tweet, while other secondary data is obtained from literature studies and documentation related to the problems studied. The conclusion obtained is that Twitter as a virtual public space is considered effective in conveying aspirations and criticism by the community